Quantitative assessment of the association between TAP2 rs241447 polymorphism and cancer risk. Issue 9 (9th May 2019) - Liu, Rongzeng; Ma, Yan; Chen, Xiafei
Abstract: The findings regarding the relation of transporter associated with antigen processing (TAP) to cancer risk have been inconsistent. The aim of this study was to comprehensively evaluate the association between TAP2 rs241447 polymorphism and cancer susceptibility. A meta‐analysis of nine investigations with 2800 cases and 1620 controls was conducted to gain a better understanding of the effect of TAP2 rs241447 polymorphism on cancer risk. Odds ratios (ORs) with 95% confidence intervals (CIs) were used to evaluate the strength of the correlation between TAP2 gene polymorphism and cancer susceptibility. The pooled results from TAP2 rs241447 polymorphism showed a decreased risk of cancer in two dominant genetic models (GG + AG vs AA: OR = 0.86, 95% CI, 0.75‐0.99; AG vs AA: OR = 0.85, 95% CI, 0.73‐0.99). From the subgroup analysis, decreased cancer susceptibility was found in Caucasians (GG + AG vs AA: OR = 0.82, 95% CI, 0.68‐0.99), especially among the subgroup of cervical carcinoma (GG + AG vs AA: OR = 0.82, 95% CI, 0.69‐0.96; AG vs AA: OR = 0.83, 95% CI, 0.70‐0.99). Overall, the results suggest that TAP2 rs241447 polymorphism contributes to decreased cancer susceptibility. Abstract : This meta‐analysis demonstrates that TAP2 rs241447 polymorphism involved in MHC I restricted antigen processing pathway is associated with a significantly decreased risk of cancer in the dominant and heterozygous models. In addition, Caucasian populations with TAP2 rs241447 polymorphism are less susceptible to cancer development than Asian populations, particularly in the case of cervical carcinoma.